Chickenpox during pregnancy: immunity, contact, and infection – a case report - Afonso Cruz, Catarina (2023)
Introduction: Varicella zoster virus primary infection during pregnancy is rare in Portugal as a result of the very high immunity rates of women of reproductive age. It is associated with higher risks of maternal complications, as well as significant fetal morbimortality, particularly if the mother acquires the infection during the first 20 weeks of gestation weeks or in the peripartum. Case description: We report a case of a 31-year-old pregnant Russian patient, G2P1, with pregnancy managed by her family doctor and an obstetrician. At 27 weeks of gestation, she had a walk-in appointment with her family doctor reporting significant contact with varicella. At the time, she did not have symptoms or significant changes at the physical examination. The patient had no previous history of chickenpox or shingles, and no record of varicella-zoster virus immunization. She was referred to the obstetrics emergency department, where she was tested for varicella zoster virus serology. It was confirmed that the patient was not immune to the varicella-zoster virus and was offered immunoglobulin administration. She developed varicella at 29 weeks and two days of gestation, without associated maternal complications or ultrasound findings suggesting the development of fetal varicella syndrome. She delivered a healthy infant at 41 weeks and two days of gestation. Comments: This case report aims to emphasize the importance of primary care physicians’ knowledge on the guidance of pregnant women who report significant varicella contact and/or develop varicella. In addition, this report highlights the importance of varicella immunity assessment at preconception counselling and care appointments to identify and manage non-immune women.